Colossal Permittivity and Low Dielectric Loss of Thermal Oxidation Single-Crystalline Si Wafers - Sun, Yalong (Materials (Basel), 2019)
In this work, thin SiO(2) insulating layers were generated on the top and bottom surfaces of single-crystalline silicon plates (n type) by thermal oxidation to obtain an insulator/semiconductor/insulator (ISI) multilayer structure. X-ray diffraction (XRD) pattern and scanning electron microscope (SEM) pictures implied that all of the synthesized SiO(2) layers were amorphous. By controlling the thermal oxidation times, we obtained SiO(2) layers with various thicknesses. The dielectric properties of silicon plates with different thicknesses of SiO(2) layers (different thermal oxidation times) were measured. The dielectric properties of all of the single-crystalline silicon plates improved greatly after thermal oxidation. The dielectric constant of the silicon plates with SiO(2) layers was approximately 10(4), which was approximately three orders more than that of the intrinsic single-crystalline silicon plate (11.9). Furthermore, both high permittivity and low dielectric loss (0.02) were simultaneously achieved in the single-crystalline silicon plates after thermal oxidation (ISI structure).